Responding to the global financial crisis: The evolution of Asian regionalism and economic globalization - Gregory Chin (Asian Development Bank Institute (ADBI), 2012)
This paper examines the evolving dynamics between economic globalization and Asian regional interdependence, and asks whether and how the global financial crisis impacted Asian regionalism. The analysis suggests that the global crisis did trigger advances in regional policy cooperation from 2007 onwards, especially in the area of financial and monetary cooperation. Although the first order response of Asian countries was to join the broader global effort to contain financial freefall at the world level, there emerged a second order response at the level of regional institutional building, specifically to "multilateralize" the Chiang Mai Initiative, and to develop a regional trust fund to help strengthen Asian bond markets. This finding reconfirms the theoretical proposition in historical institutionalism that financial crises have a catalytic effect in stimulating regional innovation. At the same time, we see evolution in the pattern of Asian regionalism in two respects: first, the recent advances in Asian regionalism are being driven primarily, at this stage, by the rise of the PRC and India - although each in their own way, and to varying degrees. The current advance in regionalism also builds on momentum provided by pre-existing programs of regional financial cooperation, namely the Chiang Mai Initiative, and "regional connectivity" programs that have also been championed by Japan and ASEAN countries, such as the GMS, CAREC, and BIMSTEC initiatives. Second, Asian economies appear to be pursuing inclusive regionalism, which attempts to strike a balance between helping themselves and helping the global economy. Asia is striving for modes of regional cooperation that are, on balance, complementary with the current global macroeconomic rebalancing agenda of the G20, and supportive of global integration and openness. The main policy findings are that Asia's future standing in an increasingly multi-centered world economy will be determined by its effectiveness in advancing a multi-layered international cooperation agenda. Yet achieving such international gains will depend on Asia's willingness to make serious advances in regional collective action and global leadership, especially in areas of financial and monetary cooperation.
Keywords: F15; F33; F36; F51; F53; F55; F59; H87; O53; 330; economic globalization; asian regional interdependence; global financial crisis; asian regionalism; Finanzkrise; Globalisierung; Regionale Wirtschaftsintegration; Finanzmarktregulierung; Internationale Wirtschaftspolitik; Asien